The Relationship Between Stress Coping, Mindfulness, and Psychological Well-Being Among the Wives of Members of the East Kalimantan Regional Police Mobile Brigade Unit (Satbrimobda Kaltim) - Evvy Wulandari; Roy Gustaf Ama (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to examine the relationships among stress coping, mindfulness, and psychological well-being among the wives of personnel serving in the Satuan Brigade Mobil Daerah Kalimantan Timur (Satbrimobda Kaltim; East Kalimantan Regional Police Mobile Brigade Unit). The wives of Mobile Brigade personnel face various psychological challenges because of the high-risk nature of their husbands' duties, frequent deployments, and limited family time. This study employed a quantitative approach with a correlational research design. The participants consisted of wives of Satbrimobda Kaltim personnel who were selected according to the established inclusion criteria. Data were collected using the Stress Coping Scale, Mindfulness Scale, and Psychological Well-Being Scale. Multiple regression analysis was conducted to examine the relationships between the independent variables and psychological well-being. The results indicated significant positive relationships between stress coping, mindfulness, and psychological well-being among the wives of Satbrimobda Kaltim personnel. Participants with more effective stress coping strategies and higher levels of mindfulness tended to report higher levels of psychological well-being. These findings suggest that stress coping and mindfulness are important factors associated with enhanced psychological well-being among the wives of Mobile Brigade personnel.